Tensor gauge boson dark matter extension of the electroweak sector - Elias Koorambas (European Physical Journal C: Particles and Fields, 2023)
Abstract The existence of dark matter is explained by a new, massive, neutral, non-symmetric, rank-2 tensor gauge boson ( $$\hbox {Z}_{{\upmu \upnu }}$$ Z μ ν -boson). The $$\hbox {Z}_{{\upmu \upnu }}$$ Z μ ν -boson can be predicted by the tensor gauge boson extension of the Electro Weak (EW) theory, proposed by Savvidy (Phys Lett B 625:341, 2005). The non-symmetric rank-2 tensor $$\hbox {Z}_{{\upmu \upnu }}$$ Z μ ν can be decomposed into a symmetric ( $$\hbox {Z}_{{(\upmu \upnu )}})$$ Z ( μ ν ) ) and anti-symmetric ( $$\hbox {Z}_{{[\upmu \upnu ]}})$$ Z [ μ ν ] ) part. Based on the non-Lagrangian formulation for the free sector of the $$\hbox {R}_{\textrm{2}}$$ R 2 -theory proposed recently by Criado et al. (Phys Rev D 102:125031, arXiv:2010.02224 , 2020), our massive anti-symmetric tensor field $$\hbox {Z}_{{[\upmu \upnu ]}}$$ Z [ μ ν ] corresponds to the massive symmetric spinor field $$\hbox {Z}_{{\upalpha \upbeta \upgamma \updelta }}$$ Z α β γ δ in the (2,0) irrep. For the massive $$\hbox {Z}_{{\upalpha \upbeta \upgamma \updelta }}$$ Z α β γ δ with the $$\hbox {Z}_{\textrm{2}}$$ Z 2 -symmetric Higgs portal couplings to a Standard Model (SM) particle, we compute the self-annihilation cross-section of the $$\hbox {Z}_{{\upalpha \upbeta \upgamma \updelta }}$$ Z α β γ δ dark matter and calculate its relic abundance. We also study the SM-SM particle scattering due to the exchange of the massive- $$\hbox {Z}_{{(\upmu \upnu )}}$$ Z ( μ ν ) symmetric field at a high energy scale. This proposition may have far reaching applications in astrophysics and cosmology.